Faktor-Faktor Customer Experience Management yang Berpengaruh terhadap Peningkatan Citra Telkom Speedy pada PT TELKOM Kandatel Bekasi - Nadhia, Aurora; Hubeis, Musa (IPB University, 2011)
Speedy as PT. Telkom Product is facing a high competition in internet services provider business. The product functional value is not sufficient to win the competition but it is need the internet service image as product image. Nowadays, Consumer perspective about product image is determined by their experiences. This is the reason behind Customer Experience Management (CEM) which defines as a process of managing customer experiences through company products or services. The factors of CEM are product, service, channel, promotion and brand. The research objectives at PT. Telkom Kandatel Bekasi are (1) to identify CEM factors of SPEEDY (2) to identify which CEM factors are influencing product image, (3) to indentify dominant CEM factor which influencing product imager (4) to recommend the effective implementation of CEM. The research showed 68,8 percent CEM factors were influencing Telkom Speedy image, which there are three factors e.g. product, promotion and brand were partially influenced Telkom Speedy image. Product was the most dominant factors of CEM which influenced image. The research recommended PT. Telkom to improve the quality of Telkom Speedy through speed of internet access improvement, front liners services, and promotion, to manage customer experience.